Oncological standards in the treatment of diffuse inflammatory diseases of the colon - Poyda, O. I.; Melnyk, V. M. (Zaporozhye Medical Journal, 2023)
Aim. To improve the effectiveness of cancer prevention and the results of surgical treatment in diffuse inflammatory diseases of the colon by identifying and using risk factors for malignancy, improving diagnostic methods, surgical strategy and tactics. Materials and methods. Using generally accepted oncological standards, 36 patients with diffuse inflammatory diseases of the colon were operated on. There were 20 (55.6 %) patients with ulcerative colitis and 16 (44.4 %) with Crohn’s disease of the colon. There were 19 (52.7 %) men and 17 (47.3 %) women. The patients’ age ranged from 21 to 56 years. When performing surgical interventions, we were guided by the studied risk factors for malignancy, the provisions of the surgical strategy and tactics, that included the indication choice, the surgical intervention extent, and the ensuring of oncoprevention. Results. The use of oncological standards, provisions of surgical strategy and tactics prevented the occurrence of postoperative mortality, malignancy of precancerous conditions, contributed to a decrease in the incidence of early postoperative complications to 5 (13.9 %), locoregional recurrence to 1 (2.8 %). Conclusions. Determination of risk factors for malignancy, improvement of diagnostic methods, surgical strategy and tactics in diffuse inflammatory diseases of the colon contribute to the timely detection of precancerous conditions, malignancy and colon cancer, justification for the feasibility of performing surgical interventions using generally accepted oncological standards. Performing surgical interventions with the use of generally accepted oncological standards, proven provisions of strategy and tactics have made it possible to prevent the occurrence of malignization of precancerous conditions, cases of postoperative mortality, reduce the frequency of early postoperative complications to 5 (13.9 %) and locoregional recurrences to 1 (2.8 %).